Through gates of garnet and gold - McGuire, Seanan (McGuire, Seanan. Wayward children, 2026)
A fan-favorite character returns in this action-packed installment of the Hugo Award-winning Wayward Children series. After Nancy was cast out of the Halls of the Dead and forced to enroll at Eleanor West's School for Wayward Children, she never believed she'd find her door again, and when she did, she didn't look back. She disappeared from the school to resume her place in the Halls, never intending to return. Years have passed. A darkness has descended on the Halls, and the living statues who populate them are dying at the hands of the already dead. The Lord and Lady who rule the land are helpless to stop the slaughter, forcing Nancy to leave the Halls again, this time on purpose, as she attempts to seek much-needed help from her former schoolmates. But who would volunteer to quest in a world where the dead roam freely? And why are the dead so intent on adding to their number?